Evolutionary Delivery Versus the "Waterfall Model" - Gilb, Tom (SIGSOFT Softw. Eng. Notes, 1985)
The conventional wisdom of planning software engineering projects, usi ng the widely cited "waterfall model" is not the only useful software development process model. In fact, the "waterfall model" may be unrea listic, and dangerous to the primary objectives of any software projec t.The alternative model, which I choose to call "evolutionary delivery " is not widely taught or practiced yet. But there is already more tha n a decade of practical experience in using it. In various forms. It i s quite clear from these experiences that evolutionary delivery is a p owerful general tool for both software development and associated syst ems development.Almost all experienced software developers do make use of some of the ideas in evolutionary development at one time or anoth er. But, this is often unplanned, informal and it is an incomplete exp loitation of this powerful method. This paper will try to expose the t heoretical and practical aspects of the method in a fuller perspective . We need to learn the theory fully, so that we can apply and learn it completely.